ENTREPRENEURSHIP REMAJA KOLOMAN PADA MASA PANDEMI COVID-19 - Fahrurrozi; Ainol Yakin; Nurul Farian (Malik Al-Shalih : Jurnal Pengabdian Masyarakat, 2022)
Entrepreneur or entrepreneurship is currently a very interesting discussion, this cannot be separated from the world conditions hit by the COVID-19 pandemic which resulted in many workers being laid off from their jobs.The objectives of the research on youth mentoring for mosque youth during the COVID-19 pandemic are: the first is to provide an entrepreneurial spirit for youth in the midst of a pandemic. The second is to provide socialization about products or services they can make and how to market them to consumers. through online media and so on.The method used in mentoring village youth entrepreneurship is by way of workshops, we invite ministers who can provide materials according to their needs related to how the product is made, until it reaches consumers through online marketing methods to payment methods via online payments. After that, participants were invited to ask questions related to the problems they faced in the pandemic era. And also at the end of the workshop participants were demonstrated to make products or services: from the initial process of making prototypes to mass production of products.The parties involved in the socialization of entrepreneurship to mosque youth are all young men and women who are still unmarried or can be said to be included in the category of teenagers, mosque takmirs, and lecturers of the Islamic economics and business faculty of IAIN Madura Pamekasan. The main target or goal in this entrepreneurship training activity is the young generation who have great potential to develop businesses so that they have a large multiplayer effect in creating new jobs. There are many potential creative ideas for running a business that have not been explored optimally.